2021
DOI: 10.3390/ph14040323
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides as Potential Anti-Tubercular Leads: A Concise Review

Abstract: Despite being considered a public health emergency for the last 25 years, tuberculosis (TB) is still one of the deadliest infectious diseases, responsible for over a million deaths every year. The length and toxicity of available treatments and the increasing emergence of multidrug-resistant strains of Mycobacterium tuberculosis renders standard regimens increasingly inefficient and emphasizes the urgency to develop new approaches that are not only cost- and time-effective but also less toxic. Antimicrobial pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 151 publications
0
11
0
Order By: Relevance
“…Several smaller antimicrobial peptide segments have been identified from antimicrobial host defense proteins with potential antimycobacterial activity. 52,53 In order to search for new smaller, nontoxic antimicrobial peptides with antimycobacterial property, we evaluated the antitubercular effect of Chem-KVL and its most nonhemolytic/nontoxic analogue, Chem-8dK, against M. tuberculosis H37Ra, Mycobacterium bovis (both slow-growing strains), and Mycobacterium smegmatis (fast-growing strain) of mycobacteria (Figure 8a−c). We found that at 16.13 μM concentration, Chem-KVL and Chem-8dK inhibited ∼80 and 95% growth of these mycobacterial strains, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Several smaller antimicrobial peptide segments have been identified from antimicrobial host defense proteins with potential antimycobacterial activity. 52,53 In order to search for new smaller, nontoxic antimicrobial peptides with antimycobacterial property, we evaluated the antitubercular effect of Chem-KVL and its most nonhemolytic/nontoxic analogue, Chem-8dK, against M. tuberculosis H37Ra, Mycobacterium bovis (both slow-growing strains), and Mycobacterium smegmatis (fast-growing strain) of mycobacteria (Figure 8a−c). We found that at 16.13 μM concentration, Chem-KVL and Chem-8dK inhibited ∼80 and 95% growth of these mycobacterial strains, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finally, a new path to bypass resistance might not arise from small drug molecules but from RNA network regulation such as ncRNA modulation ( Gerrick et al., 2018 ) or proteinaceous inhibitors that may disrupt important protein-protein interaction ( Sala et al., 2014 ), or from antimicrobial peptides ( Oliveira et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among non-animal AMPs, antibiotics produced by Lactococcus lactis exert anti-tubercular activity [ 145 ]. Especially, nisin A and lacticin 3147, as well as their mutated variants, are very effective against some MDR Mtb strains.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%